Scaling Potato Seed production in East Africa - Syngenta Foundation for Sustainable Agriculture (2019)
This short film is showcasing the impact of quality potato seed on smallholder farmers and local communities in Kenya. It describes how Kisima Farm, with some help from SFSA, grew to become one of the largest producers of certified potato seed in Kenya. With 2'000 tons of production a year, Kisima is now the largest local potato seed producer in East Africa. The aim is to show that the scale of their operation is a big part of what makes them successful and that this has encouraged other producers to imitate their business model. This is of course of great benefit to Kenya's food security and economy.